Business Adaptation Of Transnational Corporations To Russian Context: Example Of “STORA ENSO” Company - Мария Сергеевна Тысячнюк (Journal of Economic Sociology, 2010)
The focus of the paper is on the project model of constant forest use as a business strategy of transnational corporation “Stora Enso”.  It was shown how the corporation used the strategic partnership with the Foundation of wild nature in order to build good relations to all the interested parts: local population, state authorities, other companies and scientific society. The paper discloses that the corporation played the role of guide for global rules to the locality: through the certification of forest management and through the spreading its own corporate policy to the branch company. Theoretical analysis is based on the assumptions of institutional isomorphism. The study demonstrates that experience spreading on other companies of this corporation in Russia  (mimical isomorphism) faced obstacles sue to the instability of the institutional background of Russian regions during the long term period of economic reforms in Russia.